Lido-OH, a Hydroxyl Derivative of Lidocaine, Produced a Similar Local Anesthesia Profile as Lidocaine With Reduced Systemic Toxicities - Yin, Qinqin; Zhang, Weiyi; Ke, Bowen; Liu, Jin; Zhang, Wensheng (Frontiers in Pharmacology, 2021)
Back ground: Lidocaine is one of the most commonly used local anesthetics treating pain and arrhythmia. However, it could cause systemic toxicities when plasma concentration raises. To reduce lidocaine’s toxicity, we designed a hydroxyl derivative of lidocaine (lido-OH), and its local anesthesia effects and systemic toxicity in vivo quantitively investigated. Method: the effectiveness for lido-OH was studied using mice tail nerve block, rat dorsal subcutaneous infiltration, and rat sciatic nerve block models. The systemic toxicities for lido-OH were evaluated with altered state of consciousness (ASC), arrhythmia, and death in mice. Lidocaine and saline as positive and negative control, respectively. The dose-effect relationships were analyzed. Results: the half effective-concentration for lido-OH were 2.1 mg/ml with 95% confident interval (CI95) 1.6~3.1 (lidocaine: 3.1 mg/ml with CI95 2.6~4.3) in tail nerve block, 8.2 mg/ml with CI95 8.0-9.4 (lidocaine: 6.9 mg/ml, CI95 6.8-7.1) in sciatic nerve block, and 5.9 mg/ml with CI95 5.8-6.0 (lidocaine: 3.1 mg/ml, CI95 2.4-4.0) in dorsal subcutaneous anesthesia, respectively. The magnitude and duration of lido-OH were similar with lidocaine. The half effective doses (ED50) of lido-OH for ACS was 45.4 mg/kg with CI95 41.6-48.3 (lidocaine: 3.1 mg/kg, CI95 1.9~2.9), for arrhythmia was 16.0 mg/kg with CI95 15.4~16.8 (lidocaine: 3.0 mg/kg, CI95 2.7-3.3), and for death was 99.4 mg/kg with CI95 75.7~124.1 (lidocaine: 23.1 mg/kg, CI95 22.8~23.4). The therapeutic index for lido-OH and lidocaine were 35.5 and 5.6, respectively. Conclusion: compared with lidocaine, lido-OH produced local anesthesia at similar potency and efficacy, but with significantly reduced systemic toxicities.